Identification of QTLs and candidate genes for high grain Fe and Zn concentration in sorghum [Sorghum bicolor (L.)Moench]. (November 2019) - Kotla, Anuradha; Phuke, Rahul; Hariprasanna, K.; Mehtre, Shivaji P.; Rathore, Abhishek; Gorthy, Sunita; Srivastava, Rakesh K.; Das, Roma; Bhanu Prakash, A.; Radhika, K.; Hash, C. Tom; Reddy, Belum V.S.; et al.
Abstract: Sorghum is a major food crop in the semi-arid tropics of Africa and Asia. Enhancing the grain iron (Fe) and zinc (Zn) concentration in sorghum using genetic approaches would help alleviate micronutrient malnutrition in millions of poor people consuming sorghum as a staple food. To localize genomic regions associated with grain Fe and Zn, a sorghum F6 recombinant inbred line (RIL) population (342 lines derived from cross 296B × PVK 801) was phenotyped in six environments, and genotyped with simple sequence repeat (SSR), DArT (Diversity Array Technology) and DArTSeq (Diversity Array Technology) markers. Highly significant genotype × environment interactions were observed for both micronutrients. Grain Fe showed greater variation than Zn. A sorghum genetic map was constructed with 2088 markers (1148 DArTs, 927 DArTSeqs and 13 SSRs) covering 1355.52 cM with an average marker interval of 0.6 cM. Eleven QTLs (individual) and 3 QTLs (across) environments for Fe and Zn were identified. We identified putative candidate genes from the QTL interval of qfe7.1, qzn7.1, and qzn7.2 (across environments) located on SBI-07 involved in Fe and Zn metabolism. These were CYP71B34, and ZFP 8 (ZINC FINGER PROTEIN 8). After validation, the linked markers identified in this study can help in developing high grain Fe and Zn sorghum cultivars in sorghum improvement programs globally. Graphical abstract: Image 1 Highlights: This is the first report on QTL mapping utilizing high-density of DArT and DArTseq markers for identifying QTLs for grain Fe and Zn in sorghum. Putative candidate genes involved in Fe/Zn metabolism were identified within QTL with highest phenotypic effect. Identified sorghum genes within QTL interval were used to evaluate gene synteny with other cereals. Genomic regions and the candidate genes identified plays an essential role in marker-assisted breeding.